Evaluation of decommissioned liquefied natural gas storage tanks at Chula Vista, California - Lewis, James P.; Williams, Ted A. (Technical series (Nickel Development Institute (Canada)) ;, 1991)
San Diego Gas & Electric, SDG&E, built two of the first liquefied natural gas, LNG, peak shaving plants in the U.S. These plants were located on a common facility near SDG&E's South Bay power plant in Chula Vista, California, U.S.A., about 10 miles south of San Diego. The first plant went into service in 1965. A second liquefaction plant and storage tank were completed in 1970. These two plants were decommissioned in 1985 as a result of seismic evaluation based on the current perception of appropriate seismic design criteria for the site and on recent advances in dynamic structural analysis methods. The decision was made to dismantle the plants. The dismantling covered the period of April to September 1990. This publication provides the repot of decommissioning and dismantling of these facilities.